Análisis Del Desarrollo De La Gestión Del Talento Humano Y La Incidencia En El Desempeño Laboral Del Personal Administrativo Del Hospital Del IESS De Babahoyo. - Muñoz Vera, Laura Noemí (2015)
This research is born, after seeing the flaws that have public health agencies through life experiences because of this service provided, this social problem was defined as a subject of analysis for a college project. After several arguments, it came to the assessment that not all public hospitals there customer service by trained and skilled human elements, it is essential at all public agencies to improve development and employment rate of employees within their functions and these in turn with the user. Through strategies improve the service. The strategies are designed to optimize customer service and provide good service and meet public needs. Training and implementation of strategies are issues that should not be put aside in a facility, since both invest in the development of the institution as to prevent complaints by the user you must be kept satisfied that they are the reason the existence of institutions, which is why it has been desirable to develop this research.